Effects of Morinda citrifolia L. and Morinda elliptica L. leaf ethanolic extracts on fatigue and osteoarthritis - Wan Osman, Wan Nurfarahin (2016)
Morinda citrifolia (MC) has been used in folk remedies by Polynesians for over 2000 years and have a broad range of therapeutic effects. Morinda elliptica (ME) or locally known as ‘Mengkudu kecil’ used by Malaysian as medicinal plants for treatment of several health problems. This study investigated the effect of M. citrifolia and M. elliptica ethanolic leaf extracts on fatigue in mice and joint cartilage degradation in bovine explants culture and in monosodium iodoacetate (MIA)-induced osteoarthritis (OA) rats model. Exercise-induced fatigue was used to examine the anti-fatigue effects of M. citrifolia and M. elliptica leaf ethanolic extract. Balb/C female mice were divided into six groups (n=10): Control; Green tea (200 mg/kg); MCL (200 mg/kg); MCH (400 mg/kg); MEL (200 mg/kg) and MEH (400 mg/kg). The force-swim test study was assessed after six weeks of treatments. The mice were evaluated for endurance test via swimming time to exhaustion, biochemical and gene expression analyses. The swimming time was quadrupled after being treated with a high dose 400mg/kg BW of M. citrifolia compared to the control group. M. citrifolia and M. elliptica leaf extract increased liver and muscle glycogen contents and reduced blood lactic acid and blood urea nitrogen level. The extracts showed improvement in endurance capacity in mice with increased fatty acid and carbohydrate metabolism, increased in the anti-oxidant responses, decreased in substrate depletion in cell and increased in mitochondrial biogenesis. Osteoarthritis (OA) study was evaluated using monosodium-iodoacetate-induced rat model. Sprague-Dawley male rates were divided into seven groups (n=8): Healthy; non-treated OA; OA+Diclofenac (5 mg/kg); OA+MCL (200 mg/kg); OA+MCH (400 mg/kg); OA+MEL (200 mg/kg); and OA+MEH (400 mg/kg). All rats were osteoarthritis-induced by intra-articular injection of 3 mg of monosodium iodoacetate into right knee joints. After six weeks of treatments, the rats were evaluated for knee osteoarthritis via physical (radiology and histology observations), biochemical, ELISA and gene expression analyses. The rats treated with extracts showed reduction of cartilage erosion and smooth articular cartilage structure compared to the untreated rats. M. citrifolia and M. elliptica leaf extracts significantly decreased serum level of MMP1, MMP3, MMP13, PIINP, PIICP, CTXII, TNFα, IL-1β, NO and increased serum PINP compared to the non-treated group. The extracts reduced osteoarthritis progression by inhibiting the articular cartilage and collagen degradation and suppressing the inflammation responses. The extracts also improved the structure of subchondral bone which was affected in progressive osteoarthritis. It can be concluded in this study that both M. citrifolia and M. elliptica leaf extracts helped in fatigue elimination by enhancing the energy regulation and production that benefit physical activities. The extracts also protected the articular cartilage in arthritis joints by reducing the cartilage degradation and enhancing proteoglycan and collagen synthesis, providing a natural alternative treatment for osteoarthritis.